Chapter Rilievo e progetto urbano negli studi di Leonardo per Milano - Candia, Claudia (Territori, 2023)
Leonardo da Vinci surveys and sketches the city of Milan on f. 184v (c. 1493) and f. 199 (c. 1510) of the Codex Atlanticus and on f. 114r of the Codex Windsor (c. 1510). These drawings also include some projects for Milan's urban transformation. The paper describes how strongly Leonardo's idea of the city differs from the Milan of Ludovico Sforza (1494-1499) and that of the French rulers' fortification projects of 1520-1521, in particular for what concerns the revision of the external border of the city.